2001
DOI: 10.1046/j.1365-2168.2001.01701.x
|View full text |Cite
|
Sign up to set email alerts
|

Extensive surgical cytoreduction and intraoperative hyperthermic intraperitoneal chemotherapy in patients with pseudomyxoma peritonei

Abstract: These results confirm that extensive surgery combined with HIPEC is feasible in patients with pseudomyxoma peritonei and that improved long-term survival might be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
10

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(82 citation statements)
references
References 23 publications
(19 reference statements)
1
71
0
10
Order By: Relevance
“…However, a recent report described a patient with PMP responding to capecitabine -an oral fluoropyrimidine (Levitz et al, 2004). Given this, and the following rationales: (i) mitomycin C (MMC) and 5-fluorouracil (5-FU) are administered as HIPEC in the management of PMP (Witkamp et al, 2001;Sugarbaker, 2006); (ii) MMC is an established antitumour agent against gastrointestinal cancers (Crooke and Bradner, 1976;Ozawa et al, 1988); and (iii) oral capecitabine has equivalence effectiveness to bolus intravenous 5-FU/folinic acid in the treatment of metastatic colorectal cancer (Hoff et al, 2001;Van Cutsem et al, 2001), but with better patient acceptance (Borner et al, 2002), we hypothesized that a combination of concurrent MMC and capecitabine (MCap) would benefit patients with advanced PMP. Furthermore, this regimen is effective in advanced colorectal cancer (Rao et al, 2004).…”
mentioning
confidence: 99%
“…However, a recent report described a patient with PMP responding to capecitabine -an oral fluoropyrimidine (Levitz et al, 2004). Given this, and the following rationales: (i) mitomycin C (MMC) and 5-fluorouracil (5-FU) are administered as HIPEC in the management of PMP (Witkamp et al, 2001;Sugarbaker, 2006); (ii) MMC is an established antitumour agent against gastrointestinal cancers (Crooke and Bradner, 1976;Ozawa et al, 1988); and (iii) oral capecitabine has equivalence effectiveness to bolus intravenous 5-FU/folinic acid in the treatment of metastatic colorectal cancer (Hoff et al, 2001;Van Cutsem et al, 2001), but with better patient acceptance (Borner et al, 2002), we hypothesized that a combination of concurrent MMC and capecitabine (MCap) would benefit patients with advanced PMP. Furthermore, this regimen is effective in advanced colorectal cancer (Rao et al, 2004).…”
mentioning
confidence: 99%
“…Two studies 10,11 did not report whether patients entering the study were at a similar point in their disease progression, while three studies 6,12,13 were unclear. Four studies 6,10,12,13 were judged unclear on follow-up length and one study 11 did not report follow-up length. All five studies 6,10-13 were judged to be unclear when reporting whether outcomes were assessed objectively or blinding was used.…”
Section: Quality Quantity and Characteristics Of Research Availablementioning
confidence: 99%
“…Five retrospective case series reports 6,[10][11][12][13] concerning the Sugarbaker procedure met the inclusion criteria for the systematic review and are shown in Appendix 7 and Table 2. No studies examining standard debulking surgery met the inclusion criteria for the systematic review.…”
Section: Quality Quantity and Characteristics Of Research Availablementioning
confidence: 99%
“…These extensive treatments have been developed in order to remove all macroscopic lesions to enhance the efficacy of HIPEC. This aggressive treatment achieved the long term survival for selected diseases, such as pseudomyxoma peritonei and some colorectal cancers [68,69]. However, the combination of peritonectomy and HIPEC can lead to greater mortality and morbidity rates.…”
Section: Intraoperative Chemotherapy For Peritoneal Carcinomatosismentioning
confidence: 99%